Exposure to child development information with parental participation in conducting child development checks - Sumiati; A.A Putri Melastini; Yuni Kurniawati; Irma Nurma Linda; Irma Rahmayani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Parental involvement in monitoring child development is essential to detect early developmental disorders and ensure appropriate interventions. However, many parents have limited knowledge regarding developmental milestones, which hinders their participation in developmental screening activities. This study aims to analyze the relationship between exposure to child development information and parental involvement in developmental screening, including the sources of such information among mothers of toddlers. Method: A cross-sectional design involving 57 mothers of children aged 3–72 months was employed. Data were collected through structured questionnaires and analyzed using univariate statistics to describe parental participation and information sources. Bivariate analysis using the chi-square test was conducted to assess the association between exposure to developmental information and parental involvement in screening activities. Results: The majority of respondents were aged 36–50 years (54.4%), had completed secondary education (77.2%), and were unemployed (52.6%). Most respondents (57.9%) had been exposed to child development information, predominantly from health workers. Parental participation in screening was higher among mothers who had received developmental information (66.7%) than those who had not (20.8%). The association between information exposure and parental participation was statistically significant (p = 0.001). Conclusion: Exposure to developmental information significantly influences parental participation in child development screening. Parental awareness and understanding of developmental milestones are critical in supporting timely health interventions. Therefore, healthcare professionals should implement comprehensive educational efforts through various media to enhance parental engagement.